Body Mass Index and Albumin Level In Severe Preeclampsia Conservative Treatment Cases - Winarko, Esmond; Yusuf, Muhammad (Jurnal Medis Islam Internasional, 2020)
Background : Severe preeclampsia is an obstetrical problem and one of the leading cause of death in obstetric. Conservative treatment for severe preeclampsia is a complicated and risky choice, but still a considerable option to achieve a better fetal outcome. Many factors that influence the results of conservative management are complex and still very much controversial. Objective: To study the BMI and albumin level of severe preeclampsia patients who underwent conservative management in dr. Soetomo General Hospital obstetric ward in 2018 – 2019. Method: This is a descriptive cross sectional study, where the data are obtained from morning reports, obstetric ward registry and dr. Soetomo General Hospital medical record during 2018 – 2019. Results: The total conservative cases were 51 in 2018 and 69 in 2019. The majority of the patients were 20-34 years old, multigravida, non-booked cases, Javanese ethnicity, and addressed in Surabaya. Most of them were obese (with BMI ≥ 30 kg/m2) with similar BMI distribution in the successful and unsuccessful conservative management groups. Most of our patients had albumin level below 3,5 g/dl. The majority of the patients were terminated by caesarean section with the fetal outcome mostly weighed less than 2000 g. Conclusion: The majority of the patients treated conservatively were 20-34 years old, multigravida, non-booked cases, Javanese ethnicity, and addressed in Surabaya. Most of the patients have BMI ≥ 30 kg/m2 and albumin levels below 3,5.